Hambatan Guru SMA Sekecamatan Palu Selatan Dalam Mengimplementasikan Kurikulum Merdeka - Avita, Cindy Dea; Shamdas, Hj. Gamar B.N; Rafiqa; Bialangi, Mursito S.; Rauf, Abd; Budiarsa, I Made (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe the obstacles faced by biology teachers at the senior high school (SMA) level in South Palu District in implementing the Independent Curriculum. The method used was descriptive qualitative, with biology teachers from two schools in South Palu District as subjects. The research instruments were interview sheets and questionnaires. The questionnaires were analyzed using an average score calculation to determine the category of obstacles, while the interview data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing. The results of the questionnaire analysis showed that teacher obstacles ranged from low to very low. Among the three aspects, implementation had a relatively greater level of obstacles than planning and assessment, but remained in the low category, while planning and assessment were both in the very low category. Interviews supported these findings, namely that teachers still relied on training modules and experienced difficulties in adapting assessments to student characteristics, as well as facing limitations in facilities and technology. In general, it can be concluded that the obstacles faced by Biology teachers in implementing the Independent Curriculum in South Palu District are in the low and very low categories, but mentoring, competency strengthening, and infrastructure support are still needed so that curriculum implementation can run optimally.